The Great Cacti: Ethnobotany & Biogeography - Hooper, David A. (Ethnobiology Letters, 2010)
Review of The Great Cacti: Ethnobotany & Biogeography. David Yetman. 2007. The University of Arizona, Tucson. Pp. 320, 366 color photographs, 17 maps. 59.95 (cloth). ISBN 9780816524310.